Psychological compatibility of Riyadh children and its relationship to aggressive behavior - Obaid, Amal Hammoudi (Al-Adab Journal, 2015)
Targeting the current research is to detect psychological adjustment among children Riyadh and its relationship to aggressive behavior included research sample (120) children from children Riyadh for the academic year 2013-2014 and to achieve the objectives of the research were used samples t-test for two independent samples of equal number, and the use of test samples t for one sample to measure the psychological adjustment and measurement of aggressive behavior and the use of Pearson’s correlation coefficient to know the relationship between psychological adjustment and aggressive behavior, was extracting reliability and validity. The research and having reverse correlation results as the greater psychological adjustment Say aggressive behavior in children Riyadh, was the female have myself better than males agree, but for aggressive behavior was when the male is higher than in females, and resulted in findings that children of kindergarten have myself compatibility and the lack of they have aggressive behavior of children, unlike the preliminary stage. Finally, the researcher made some recommendations and suggestions for other studies.